2009
DOI: 10.1021/am900573q
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Annealing-Induced Self-Organization of Poly(3-hexylthiophene), a High-Performance Electrochromic Material

Abstract: We have systematically studied the self-organization of poly(3-hexylthiophene) (P3HT), an electrochromic material, upon control of the solvent evaporation rate. We characterized these polymer films using atomic force microscopy and X-ray diffraction measurements. Well-ordered P3HT structures were developed after solvent annealing; these highly crystalline structures exhibited enhanced electrochromic contrast and reduced resistance within the film, leading to larger coloration efficiencies and faster switching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 51 publications
1
41
0
Order By: Relevance
“…An EC material with a high coloration efficiency can provide a large transmittance mod- ) [17,18]. "Switching time" is the amount of time required to pass most of the charge when a voltage change is applied [32]. The switching kinetics of the nanofiber based ECDs was investigated by chronoamperometric (CA) measurements.…”
Section: Resultsmentioning
confidence: 99%
“…An EC material with a high coloration efficiency can provide a large transmittance mod- ) [17,18]. "Switching time" is the amount of time required to pass most of the charge when a voltage change is applied [32]. The switching kinetics of the nanofiber based ECDs was investigated by chronoamperometric (CA) measurements.…”
Section: Resultsmentioning
confidence: 99%
“…4b) revealed that the typical quasi-reversible electrochemical behavior of the polymer is preserved in the composite [35]. By comparing the cyclic voltammograms of the SWCNT array and the hybrid material, a significant difference was observed (Fig.…”
Section: Potentiodynamic Synthesis Of P3ht/swcnt Array Compositesmentioning
confidence: 91%
“…The peak intensity was further increased only by 1.8 times after the film was annealed which was much less than those of PCBM, OIBC60P, and OIB2FC60P. Furthermore, a peak at 8.82°was found which was assigned to the crystallization peak of fullerene derivative OIHC60P [44,48]. The XRD results of P3HT/ OIHC60P blend films indicated that OIHC60P was easy to self aggregation and then induced the crystallization of the P3HT in the as-cast films.…”
Section: Xrd Spectramentioning
confidence: 95%
“…5.5°, which meant the existence of the crystal regions of P3HT in all the blend films [43]. The 2h angles of the maximum diffraction peak of the ascast films were all greater than those of annealing films, which indicated that the mean interlayer spacing for the as-cast blend films was less than that of the annealing ones [44]. As shown in Table 1, the FWHM (b) of the blend films were decreased after the films were annealed, which indicated that the mean size of the ordered domains (s) in the blend films were increased according to the Scherrer equation.…”
Section: Xrd Spectramentioning
confidence: 95%